Clinical effect of a novel transpedicular reducer for reduction and bone grafting combined with pedicle screw fixation for thoracolumbar burst fractures - Cai, Menghan (BMC Musculoskelet Disord, 2021)
BACKGROUND: Short-segment transpedicular screw fixation is a common method for the treatment of thoracolumbar burst fractures (TBFs),but this technique has many problems. Therefore,the purpose of this article is to observe and evaluate the clinical efficacy of a novel transpedicular reducer that we designed for fractured vertebral body reduction and bone grafting in the treatment of TBFs. METHODS: From July 2018 to November 2020, 70 cases of TBFs were included. Thirty-five patients were treated with the novel transpedicular reducer for reduction and bone grafting combined with pedicle screw fixation (observation group), and 35 patients were treated with short-segment transpedicular screw fixation (control group). Before the operation, after reduction, and 3 days, 3 months,and 12 months after the operation, the two groups were assessed, and compared with respect to the anterior and middle heights of the injured vertebrae, the ratios of the anterior and middle heights of the injured vertebral body to the respective heights of the adjacent uninjured vertebral bodies (AVBHr and MVBHr, respectively), and the Cobb angle of the patients. We compared the pain VAS score and quality of life GQOL-74 score at the last follow-up. Finally,we evaluated the distribution of bone grafts and bone healing 12 months after the operation. RESULTS: The anterior height, middle height, AVBHr, MVBHr, and Cobb angle of the injured vertebral body in the observation after reduction, and 3 days, 3 months and 12 months post-operatively were compared with those of the injured vertebral body before operation. All of these parameters were improved, and the difference was statistically significant (p < 0.05). These parameters in the observation group at the above time points were significantly better than thoes in the control group at the corresponding time points (p < 0.05). The VAS scores at the last follow-up were significantly better than those of the control group (p < 0.05), but the GQOL-74 score differences were not statistically significant (p > 0.05). The observation group showed no obvious defects on CT at 12 months after the operation, and the bone healing was good. CONCLUSION: The novel transpedicular reducer for reduction and bone grafting combined with pedicle screw fixation for TBFs has good clinical efficacy.